2010
DOI: 10.3109/02713683.2010.507903
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between the Thr431Asn and Arg83Lys Polymorphisms of theROCK2Gene and Diabetic Retinopathy

Abstract: These results suggest that there were no evidence for an association of ROCK2 gene Thr431Asn and Arg83Lys polymorphisms with diabetes or diabetic retinopathy in the Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…No evidence for an association of ROCK2 gene rs2230774 (Thr431Asn) and rs1130757 (Arg83Lys) polymorphisms with diabetic retinopathy has been reported in a Turkish Population [31]. Additionally, the haplotypes are not signiicantly associated with diabetic retinopathy as shown in this study [31].…”
Section: Ocular Diseasesmentioning
confidence: 50%
See 4 more Smart Citations
“…No evidence for an association of ROCK2 gene rs2230774 (Thr431Asn) and rs1130757 (Arg83Lys) polymorphisms with diabetic retinopathy has been reported in a Turkish Population [31]. Additionally, the haplotypes are not signiicantly associated with diabetic retinopathy as shown in this study [31].…”
Section: Ocular Diseasesmentioning
confidence: 50%
“…It has been reported that ROCK2 gene rs2230774 (Thr431Asn) and rs1130757 (Arg83Lys) polymorphisms were not associated with the risk of diabetes (mainly type-2) [31], suggesting that these polymorphisms are not a contributing factor to the susceptibility of diabetes in a Turkish population. However, Ross [23] presented evidence for the association of ROCK2 rs1868584 variant with type-1 diabetes.…”
Section: Diabetesmentioning
confidence: 99%
See 3 more Smart Citations